Chemical neurotoxicity to the inferior alveolar nerve—A rare sequela of endodontic treatment. (5th April 2022) - Mahmood, Hanya; Hoare, Johnathan; Atkins, Simon
Abstract: Aim: Damage to the inferior alveolar nerve (IAN) during endodontic procedures is a rare complication. However, over‐ instrumentation and over‐filling during root canal treatment can cause injury through direct trauma, pressure or neurotoxicity from intra‐canal irrigants or root canal filling materials, particularly where the roots of mandibular molars or premolars are in close proximity to the IAN. This report describes the clinical presentation and management of a severe chemical injury to the right IAN following the endodontic treatment. We also provide practical considerations to help minimise such complications. Methods: A 27‐year‐old female developed immediate onset numbness and tingling to the right mental region following endodontic treatment of tooth 47. Radiographic examination confirmed widespread extrusion of root canal sealer within the marrow spaces of the right mandibular body extending centrally within the mandibular canal and perforating the lingual cortex. Results: Urgent surgical exploration and decompression of the right IAN were undertaken, which revealed an avascular and fibrotic nerve with virtually no normal neuronal structure. There was evidence of foreign material both in contact with the epineurium and within the nerve trunk, much of which could not be eliminated. This severe chemical insult to the nerve resulted in irreversible anaesthesia in the right IAN distribution. Conclusion: This case highlights the diligence that is required when performing root canal treatment in high‐risk mandibular molar teeth, particularly in relation to confining materials within the canal space, accurate canal measurements and comprehensive radiographic evaluation both pre‐ and post‐operatively. Urgent specialist referral for the elimination of foreign material is essential to maximise the potential for nerve regeneration.